Some aspects of the reproduction of the elongate sunset clam, Gari Elongata (Lamarck 1818) from the Banate Bay area West Central Philippines. - Nabuab, Fenelyn M.
Gari elongata, the elogate sunset clam, is an estuarine to marine species that was reportedly able to adapt to freshwater habitats. Reproduction of this species from the Banate Bay Area, West Central Philippines was studied. G. elongata is a delicious bivalve with occasional incidences of hermaphrodites and exhibits ab incubatory behavior. It has large mature oocytes (103um smear and 86-88um in prepared slides) which are typical of larvae that have a direct development. Sex ratio in the canal is 1M: 1.06F which does not significantly depart from the expected ratio (1M: 1F) while in the pond sex ratio is 1M : 1:23F which is highly skewed to female. Sexual maturity of G. elongata in the pond is attained at 44.80mm and 59.10mm in female and male, respectively. On the other hand, those in the irrigation canal reached maturity at 43.15mm and 43.70mm in female and male, respectively. These show that females mature first compared to males and that clams in the canal mature early than the clams in the pond. Five determinate gonad stages based on histological examination were described in male and female clams: developing, mature, partially spawned, redeveloping and spent. Interminate or immature gonads were also observed. Reproductive cycle of G. elongata is protracted or continous. In the irrigation canal, multiple peaks were observed in the reproductive cycle with the highest on wet months. On the other hand, in the pond, maturation and spawning occurred on dry months and development on wet months. This variation may be due to the differences in the water dynamics in both sites which affect phytoplankton density/nutritional status which consequently affect reproductive cycle of this species. Intraspecific variation in the reproduction of this species between the two sites might be an expression of phenotypic plasticity in response to the differences in the local conditions (Haag and Staton 2003). In terms of management measures, collection of individuals smaller than 43mm must not be conducted and collection must also be regulated during maturation and spawning months. In summary, G. elongata exhibits a mosaic of marine and freshwater reproductive characteristics which allows the survival of this species in an environment where water regime is unpredictable and prone to disturbance.